EXPLORING THE EFFECTIVENESS OF DIVERSITY, EQUITY, AND INCLUSION (DEI) ON EMPLOYER BRANDING - Ansari, Iram-Sultana Shahbaaz; Phadnis, Anuradha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
To promote fairness and reduce prejudice, diversity, equity, and inclusion, or DEI, is a critical component of modern public conversation. Brands are using it more and more to communicate their personality and reflect the principles of their target audience. But putting DEI into practice as a brand approach to leadership demands more than just empty promises and may be dangerous if not fully accepted. DEI projects may be seen by clients as being unauthentic or failing to resonate with their intended audiences. Companies, advertisers, authorities, and lawmakers should take into account important factors and potential, as well as current customer and brand views, to get a better understanding of the function of DEI in managing a company.